The Effect of Corporate Governance on Investor Reaction in Mediation of Internet Financial Reporting - Puspaningrum, Faluthia Fitri; Priono, Hero; Sulistyowati, Erna; Muslimin; Hidajat, Sjarief (Future Science, 2020)
Internet Financial Reporting can help investors more quickly access company information as a basis for decision making. The sooner the information will make it easier for investors to react. Investor's reaction to information is indicated by a reaction to information that is valuable to investors, both good news or bad news. Corporate governance has developed as a reaction to various corporate failures as a result of bad corporate governance, so that information about corporate governance in the company can cause investor reactions, because the good or bad implementation of corporate governance in the company is one of the factors in decision makings, especially in investing in a company. This study aims to analyze and prove the effect of corporate governance on investor reaction mediated by internet financial reporting. The method used in this research is the quantitative method. The object of research used is companies included in Indonesia's Corporate Governance in collaboration with SWA magazine for the period 2013 - 2017. The population in this study is ninety-nine companies that are included in the Indonesian of Corporate Governance in collaboration with SWA magazine for the period of 2013 - 2017. To determine the research sample, the probability sampling method is used. The samples in this study were eight companies that were included in the Indonesia Most Trusted Company ranking in Indonesia's list of Corporate Governance in collaboration with SWA magazine for the period 2013-2017. Data collection techniques used were secondary data collection techniques, namely data obtained indirectly by studying documents related to research. Secondary data in the form of data on company financial statements included in Indonesia's of Corporate Governance in collaboration with SWA magazine for the period 2013 - 2017 published on the official website of the IDX. The analytical method used is Partial Least Square (PLS) which is assisted with Warp PLS 6.0 software. The results showed that Corporate Governance does not affect Internet Financial Reporting; Corporate Governance does not affect Investor Reaction; Internet Financial Reporting affect Investor Reaction, and Internet Financial Reporting does not mediate Corporate Governance to Investor Reactions.